2017
DOI: 10.18052/www.scipress.com/ijet.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanoparticle Enhanced Lubricant Films in Dynamic Properties of Plain Journal Bearings at High Reynolds Numbers

Abstract: Abstract. The aim of this paper is numerical analysis of plain journal bearing with Nano particle added lubricating oil. The fluid film bearing is studied with the modified Reynolds equation which considered time dependent inertia effects at rotating speeds with the linearized turbulence. The research is performed for numerous nano-fluids include nanoparticles of CuO, TiO 2 , Ag and Cu and SAE 20W50 as a base fluid. The time transient governing equations include the incompressible mass conservation equation, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A single porous-layered journal bearing be made up of a permeable bush (contains fine particles of size 2.5 μm) is fitted with an impermeable bearing housing and a journal, as indicated in Figure 1. The mathematical analysis of such bearing system requires some assumptions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the porous layer and hydrodynamic nano-fluid film. These are given below.…”
Section: Mathematical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…A single porous-layered journal bearing be made up of a permeable bush (contains fine particles of size 2.5 μm) is fitted with an impermeable bearing housing and a journal, as indicated in Figure 1. The mathematical analysis of such bearing system requires some assumptions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the porous layer and hydrodynamic nano-fluid film. These are given below.…”
Section: Mathematical Evaluationmentioning
confidence: 99%
“…They also stated that the capacity of said bearing to carry the load increases with the application of magnetic fluid and also shifted pressure centre towards the inlet for reducing the friction. Jamalabadi [17] numerically analysed a nano-fluid lubricated plain journal bearing with long and short bearing approximation. The addition of nanoparticles (like CuO, TiO2, Ag and Cu) on to the base lubricant, results in an increase in fluid stiffness, damping ratio and mass coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…1. The scientific explanation of such a bearing framework requires a few suspicions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]26] of the porous layer and hydrodynamic nano-oil film. These are given underneath.…”
Section: Mathematical Evaluationmentioning
confidence: 99%
“…The volume portion of nanoparticles is straightforwardly corresponding with the capacity to carry the load and contrarily relative with the frictional coefficient. Bhat et al [15] assessed the mathematical expression of pressure, pressure centre, frictional power, load limit, and coefficient of contact on account of magnetic fluid greased up porous composite slider bearing. They likewise expressed that the loadcapacity increments with the utilization of magnetic fluid and shifted pressure centre towards the inlet for decreasing the contact friction.…”
Section: Introductionmentioning
confidence: 99%
“…In present research, with using computational fluid dynamic (CFD) thermohydrodynamic (THD) numerical simulations [27], the effect of nanoparticles on the performance characteristics of plain journal bearings is evaluated. Particularly, 3D simulation of a journal bearing is implemented using CFD which considerably improves the accuracy of results, coupled with conjugate heat transfer model for metal parts of bearings [28]. It is shown that the spatial temperature distribution in the lubricant film is accurately calculated.…”
Section: Introductionmentioning
confidence: 99%